Numerical Analysis of Patrol Boat Performance with a Stern Flap - Edi Jadmiko; Sunarsih; Jayanti Wulandari (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2020)
Ship resistance signifies the amount of fluid force acting opposes the ship movement. Past researches revealed that installation of a stern flap reduces the value by 5% to 10%. The current research investigates resistance reduction on a patrol boat due to variation of the flap span width and angle of installation. The flap chord length was varied by 50% and 100% of the ship transom width (BT) whilst the installation angle was set to 00 and 50. Numerical tests were carried out using CFD method employing NUMECA Fine Marine software. Simulation result disclosed that the stern flap length of 50% BT installed at 00 indicates the most optimum arrangement. Reduction of the resistance value increases correspondingly to the ship resistance as the ship speed increases. The wave form developed conforms with the flap width such that the wider the flap results in wider wave form. A reduction at the most of 1.87% was yielded at 15 knot ship speed. No significant reduction was observed due to installation angle at 00 and 50.